Mindfulness and nutritional counseling in promoting awareness of eating behavior: integrative review (Research, Society and Development, 2021)
Objective: To identify the effectiveness of mindfulness and nutritional counseling in promoting eating behavior. Method: This is an integrative review, carried out between August and September 2020, with searches in the BVS and Pubmed databases. The following descriptors were used: mindfulness, eating behavior and adult, in English, Portuguese and Spanish. Results: seven articles composed the study sample. All studies performed interventions of mindfulness associated with nutritional counseling. The results obtained demonstrate the effectiveness of this intervention in the behavior and dietary choices, in reducing weight in obese patients, contributes to improve the quality of life and promote greater food awareness. The interventions obtained high acceptance. Final considerations: The practice of mindfulness associated with nutritional counseling proved effective to promote food awareness and adopt a healthier eating behavior, bringing numerous benefits to the quality of life of those who practice it.